A minimally-invasive method for sampling human petrous bones from the cranial base for ancient DNA analysis. (June 2017) - Sirak, Kendra A.; Fernandes, Daniel M.; Cheronet, Olivia; Novak, Mario; Gamarra, Beatriz; Balassa, Tímea; Bernert, Zsolt; Cséki, Andrea; Dani, János; Gallina, József Zsolt; Kocsis-Buruzs, Gábor; Kővári, Ivett; et al.
Ancient DNA (aDNA) research involves invasive and destructive sampling procedures that are often incompatible with anthropological, anatomical, and bioarcheological analyses requiring intact skeletal remains. The osseous labyrinth inside the petrous bone has been shown to yield higher amounts of endogenous DNA than any other skeletal element; however, accessing this labyrinth in cases of a complete or reconstructed skull involves causing major structural damage to the cranial vault or base. Here, we describe a novel cranial base drilling method (CBDM) for accessing the osseous labyrinth from the cranial base that prevents damaging the surrounding cranial features, making it highly complementary to morphological analyses. We assessed this method by comparing the aDNA results from one petrous bone processed using our novel method to its pair, which was processed using established protocols for sampling disarticulated petrous bones. We show a decrease in endogenous DNA and molecular copy numbers when the drilling method is used; however, we also show that this method produces more endogenous DNA and higher copy numbers than any postcranial bone. Our results demonstrate that this minimally-invasive method reduces the loss of genetic data associated with the use of other skeletal elements and enables the combined craniometric and genetic study of individuals with archeological, cultural, and evolutionary value.